Policy Implications of Refugee Education in Urban Settings: A Case Study of the Experience of Refugee Community-Based Schools in Cairo - Mayom, Dawood (AUC Knowledge Fountain, 2021)
Egypt hosts asylum-seekers and refugees originating from a large number of countries. Many refugees find themselves living in urban settings, and education and access to schools across various levels have increasingly become challenging for children. This study focuses on refugees’ education between the years 2011-2020 in Cairo. During these years, the number of students increased by five times, making the provision of education a challenging endeavor. The research aims to explore and understand the multiple barriers to Community-Based Refugee Education in Urban Egypt. This study used a qualitative case study because of its relevancy to this topic and context. The techniques for this research and instruments of data collection are interviews, focus group discussion, and participant observations. The purposive samples included parents of refugee students, refugee school headmasters, and educational services providers. The participants were chosen based on their specific characteristics and educational experiences. The findings shed light on six emerging themes discussing the experiences of community school centers in Greater Cairo: accessibility to education, affordability of education, quality of education in refugee community-based schools, accountability and protective learning environments, system strengthening and partnership, and good-practice models. Tackling these challenges, towards this end, the research generates several policy recommendations to enhance refugee access to education in Egypt.